Exploring the Psychometric Properties of the Current Opioid Misuse Measure Among Adults With Chronic Pain and Opioid Use. Issue 8 (August 2020) - Rogers, Andrew H.; Gallagher, Matthew W.; Jamison, Robert N.; Zvolensky, Michael J.
Abstract : Objectives: The opioid epidemic is a significant public health problem that is associated with overdose and death. The increase in opioid-related problems can largely be attributed to increases in opioid prescriptions for the treatment of chronic pain. Unfortunately, there is not a consensus on a definition of opioid misuse in the context of chronic pain, making measurement a challenge. One commonly used measure to assess opioid misuse in the context of chronic pain is the Current Opioid Misuse Measure (COMM). The COMM was designed to assess opioid misuse generally, as captured by psychiatric symptoms and aberrant drug use behaviors. Although studies have examined cross-validation using correlations, little psychometric work has been conducted, and therefore it is currently unknown what domains the measure is assessing. Materials and Methods: The current study examined the factor structure of the COMM using confirmatory and exploratory factor analysis among 445 opioid-using adults with chronic pain. Results: The results did not support the widely accepted 1-factor opioid misuse solution; rather they supported a 2-factor, psychiatric problems and aberrant-drug-use-problems factor structure. Convergent and divergent validity were also examined at the bivariate level. Discussion: Given the importance and relevance for opioid misuse in the context of chronic pain, it is important for researchers to continue assessing and providing psychometric evidence for the COMM.